Furfural Biodegradation in a Moving Bed Biofilm Reactor Using Native Bacteria and Agroforestry Waste as Supports - Farías, Alejandro Rubén (2025)
Furfural is a relevant industrial product, but its presence in water and soil generates contamination and health risks. Moving bed biofilm reactors (MBBR) are an increasingly used alternative to eliminate contaminants with the advantage of occupying small spaces, despite their highly dependence on support and microorganisms involved in the process. This work proposes furfural elimination through a laboratory-scale MBBR using Bacillus licheniformis GTQ1, Microbacterium sp. GISTAQ2 and Brevundimonas sp. GISTAQ1 isolated from an industrial effluent and agroforestry waste (rice husks, pine sawdust and quebracho chips) as supports. Biofilm development was tested with both axenic and mixed cultures, confirming high coverage by Scanning Electron Microscope (SEM) images, especially in triple mixed cultures. Biodegradation tests were carried out in the MBBR with 15 g rice husk or quebracho chips as supports and 4000 mg L-1 initial furfural concentration for 72 h. The mixed culture achieved almost a 100% furfural removal in three days with a rate of 3.97% per h with rice husk and 2.61% per h with quebracho chips. This laboratory scale MBBR-development is a promising first step ready for a scale-up for its implementation in industries to significantly reduce the environmental impact of the discharge of this type of effluents.